High prevalence of colorectal neoplasm in patients with non-alcoholic steatohepatitis - Wong, Vincent Wai-Sun; Wong, Grace Lai-Hung; Tsang, Steven Woon-Choy; Fan, Tina; Chu, Winnie Chiu-Wing; Woo, Jean; Chan, Anthony Wing-Hung; Choi, Paul Cheung-Lung; Chim, Angel Mei-Ling; Lau, James Yun-Wong; Chan, Francis Ka-Leung; Sung, Joseph Jao-Yiu; et al. (Gut, 2011)
ObjectiveNon-alcoholic fatty liver disease (NAFLD) affects 20–40% of the general adult population. Due to shared risk factors, it is postulated that NAFLD patients have an increased risk of colorectal neoplasm and should be a target group for screening. The aim of this study was to examine the prevalence of colorectal neoplasm in NAFLD patients and the risk of colorectal neoplasm in relation to the severity of NAFLD histology.DesignCross-sectional study.SettingUniversity hospital with case recruitment from the community and clinics.PatientsSubjects aged 40–70 years were recruited for colonoscopic screening from two study cohorts: (1) community subjects; and (2) consecutive patients with biopsy proven NAFLD. In the community cohort, hepatic fat was measured by proton-magnetic resonance spectroscopy.Main outcome measuresPrevalence of colorectal adenomas. Advanced colorectal neoplasm was defined as cancer or adenomas with villous architecture or high grade dysplasia.ResultsNAFLD patients (N=199) had a higher prevalence of colorectal adenomas (34.7% vs 21.5%; p=0.043) and advanced neoplasms (18.6% vs 5.5%; p=0.002) than healthy controls (N=181). Thirteen of 29 (45%) NAFLD patients with advanced neoplasms had isolated lesions in the right sided colon. Among patients with biopsy proven NAFLD, patients with non-alcoholic steatohepatitis (N=49) had a higher prevalence of adenomas (51.0% vs 25.6%; p=0.005) and advanced neoplasms (34.7% vs 14.0%; p=0.011) than those with simple steatosis (N=86). After adjusting for demographic and metabolic factors, non-alcoholic steatohepatitis remained associated with adenomas (adjusted OR 4.89, 95% CI 2.04 to 11.70) and advanced neoplasms (OR 5.34, 95% CI 1.92 to 14.84). In contrast, the prevalence of adenomas and advanced neoplasms was similar between patients with simple steatosis and control subjects.ConclusionsNon-alcoholic steatohepatitis is associated with a high prevalence of colorectal adenomas and advanced neoplasms. The adenomas are found more commonly in the right sided colon. Colorectal cancer screening is strongly indicated in this high risk group.